Respuesta :
[tex]x - y = 7 \\ y = 3x + 12[/tex]
First
[tex]x - y = 7 \\ x = 7 + y[/tex]
Substitute that into
[tex]y = 3(7 + y) + 12 \\ y = 21 + 3y + 12 \\ 2y = - 33 \\ y = - \frac{33}{2} [/tex]
Substitute that into
[tex]x = 7 + ( - \frac{33}{2} ) \\ x = \frac{14}{2} - \frac{33}{2} \\ x = - \frac{19}{2} [/tex]
x = -19/2, y = -33/2
Hope this helps. - M
We will solve the system by substitution, the solution is (-9.5, -16.5).
How to solve a system of equations?
Here we have the system of equations:
x - y = 7
y = 3x + 12
To solve it, first, we need to isolate one of the variables, and then replace that in the other equation. We already have y isolated on the second equation, so we can replace it on the first one.
x - y = 7
x - (3x + 12) = 7
x - 3x - 12 = 7
-2x - 12 = 7
-2x = 7 + 12 = 19
x = 19/-2 = -9.5
Now that we know the value of x, we can use one of the equations to find the value of y.
y = 3*(-9.5) + 12 = -16.5
Then the solution is (-9.5, -16.5).
If you want to learn more about systems of equations, you can read:
https://brainly.com/question/13729904